DEVELOPMENT OF SODA API LEARNING MEDIA BY APPLYING JIGMENT LEARNING METHODS FOR CITIZEN STUDENTS EARNING - Binti Mahmudah; Ida Putri Rarasati; Muhammad Iqbal Baihaqi (JOSAR (Journal of Students Academic Research), 2022)
In every learning carried out in an educational institution, the best thing is always done to improve the results of the learning. In this case learning can be assisted by learning media. The learning media can increase students' absorption in receiving each subject matter. For its use, the media used is SODA API media. This SODA API media has characteristics that can improve teamwork. Referring to the application of this learning media, it is applied to SMAN 4 Blitar. It is hoped that the results of its implementation can be; (1) developing the effectiveness and efficiency of learning, (2) developing students' enthusiasm for learning, (3) developing students' interest and motivation in learning, (4) developing students interact directly with reality, (5) overcoming the diverse learning modalities of students, (6) streamline the communication process in learning, (7) improve the quality of learning. This learning media will be optimized for the JIGMEN learning method which will certainly help students absorb the material presented.